2001
DOI: 10.1002/app.1683
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the tribological properties of polyamide 6 filled with molybdenum disulfide and liquid crystalline additives

Abstract: ABSTRACT:The effect of adding a 1 wt % proportion of thermotropic liquid crystals 4,4Ј-dibutylazobenzene (LC1) and 4-octyl, 4Ј-cyanobiphenyl (LC2) on the tribological properties of polyamide 6 (PA 6) is compared with that of the addition of MoS 2 in different concentrations (1 and 5 wt %). Friction and wear are determined in a pin-ondisk tribometer by using injection-molded additivated nylon disks against steel or aluminum pins, below (25°C) and above (80°C) glass transition temperature. Polymeric blends are c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
10

Year Published

2002
2002
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 17 publications
2
19
0
10
Order By: Relevance
“…Pin-on-disk tests for PS and SAN show that 1 wt% of a MLC improves the wear resistance of these polymers [12,15]. Similar results for PA6 [13] reveal a similar or even superior antiwear property compared to the well known solid lubricant MoS 2 .…”
Section: Introduction and Scopesupporting
confidence: 73%
See 4 more Smart Citations
“…Pin-on-disk tests for PS and SAN show that 1 wt% of a MLC improves the wear resistance of these polymers [12,15]. Similar results for PA6 [13] reveal a similar or even superior antiwear property compared to the well known solid lubricant MoS 2 .…”
Section: Introduction and Scopesupporting
confidence: 73%
“…We have previously reported [13,15] tribological properties of PS and SAN with LC1 additions in pin-on-disk tests against AISI 52100 steel under variable load, speed and sliding distance. We have found that addition of 1 wt% LC1 produces a dynamic friction reduction with respect to pure PS between 10 and 14%, depending upon test variables.…”
Section: Friction Resultsmentioning
confidence: 98%
See 3 more Smart Citations